Challenges of the Bungo Muhammadiyah Student Association (IMM) Organization in Recruiting New Members - Hidayat, Husnil; Junaidi, Junaidi; Azis, Agus Fadilah (PERSPEKTIF, 2025)
This Research aims to diagnose the decline in IMM members at Muara Bungo Muhammadiyah University. This condition can also cause the Muhammadiyah cadre formation not to run well. This research method uses a qualitative approach with interview techniques with credible sources at IMM, namely the IMM PC Instructor Corps and the Chair of PC IMM Bungo for 2023-2024. Results From this Research, several obstacles were found that led to a decrease in the number of IMM members. Obstacles faced include students not understanding the function of organizing, negative stigma towards organizations, dividing time between academics and organizations, the benefits of organizing academically not yet visible, organizational activities still monotonous and seem uninteresting, internal obstacles within the organization itself, and competition with other student organizations outside campus. The findings from this Research can be used as evaluation material for PC IMM Bungo administrators to create more varied work programs that are relevant to student development so that students are interested in becoming members. The implications contribute to the programs that will be carried out and which can be maximized so that IMM can become an organization with integrity.